Pengetahuan, sikap, dan ketrampilan konselor kontrasepsi mantap - Sadli, S. (Perkumpulan Kontrasepsi Mantap Indonesia, 1988)
Psychological approach by the staff of family planning program in Indonesia in counseling their clients; papers.